Yeasts and Their Derivatives as Functional Feed Additives in Poultry Nutrition - Wafaa A. Abd El-Ghany (Agriculture)
Restrictions on antimicrobial use in food animal production have been imposed due to concerns over residue accumulation and the development of antibiotic resistance. Thus, there is a need to find potential and safe alternatives to antimicrobials. Some of these natural alternatives include yeasts and their derivatives. Yeasts are single-cell facultative anaerobic ascomycetous eukaryotic fungi that are comprehensively incorporated into poultry nutrition for their potential beneficial effects. They are available as probiotics (whole living yeast cells) or as prebiotics (bioactive derivative components, such as mannan-oligosaccharides, β-glucans, or chitin), along with nucleotides found in distillery yeast sludge or hydrolyzed yeast. The beneficial effects of yeasts and their derivatives stem from their ability to enhance production performance, stimulate immune responses, modulate gut microbiota, and reduce oxidative stress. This review explores the potential roles of yeasts and their derivatives in poultry nutrition. Their effects on productive performance (in broilers, layers, and breeders), carcass traits, immune response, gut health, and oxidative stress are investigated.